Taking the Lead: Initiating Change as a New Chairperson - Craig D Hlavac (Academic Chairpersons Conference Proceedings, 2017)
Academic department chairpersons are often asked to lead without management training, prior experience, or formal mentorship. These same chairpersons are frequently faced with initiating change in departments that have operated similarly for years – perhaps decades. What is the first step? What should a new chair do to begin the discussion about change without alienating the faculty? This session will provide participants with practical, research-based strategies for defining the roles of the chair position, building trust within the faculty, and beginning a dialogue focused on meaningful change. Opportunities for small-group discussion as well as scenario-based discourse will be included.
Keywords: Leadership; Change; Organization; Data Analysis; Communication